The Development Of Nurse Anesthetists’ Competency Assessment Scale, Phramongkutklao Hospital - สะอาดไหว้, ปาณิสรา; วิวัฒน์วานิช, สุวิณี (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this research was to develop and set standards for nurse anesthetists’ competency scale in Phramongkutklao hospital. The research was conducted in two main phases. The first phase was consisted of 2 steps. The first step was to explore and to select the essential nurse anesthetists’ competency by using focus group.The second step was to construct the competency scale by using the Behaviorally Rubrics score, testing the content validity index by 7 experts, then testing the quality of the instrument by inter-rater reliability and Hoyt, s analysis of variance, which was tested by 7 nursing anesthetists directors, 45 nurse anesthetists. The second phase was to cut-off point by 7 nurse anesthetists’ experts. The results are as follows: The nurse anesthetists’ competency scale in Phramongkutklao hospital consisted of 6 domains 43 items. The 6 domains are patient care before anesthesia(7items), patient care between anesthesia(13items), patient care after anesthesia(8items),use and maintain medical equipment(5items), coordinate communication(5items), develop quality(5items). The quality-testing results of instrument are as follow; CVI is 1, inter-rater reliability is .96 and Hoyt, s analysis of variance is .99. The cutting point of nurse anesthetists’ competency scale in Phramongkutklao hospital is T38.87